ANALISA THERMAL GRAVIMETRIC ANALYSIS BAHAN BAKAR EMULSI AIR - Agung Sudrajad; Ipick Setiawan (FLYWHEEL : Jurnal Teknik Mesin Untirta, 2015)
The fuel that we use in the subsistence component containing air pollutants. To overcome these problems the researchers and engineers to create a way for the fuel used was clean and friendly environment. One method used is a water emulsion. This study aims to identify the characteristics of the water emulsion fuel. This study is determine the characteristics of the water emulsion fuel through testing Thermal Gravimetric Analysis (TGA). From the test results it can be seen pure diesel fuel MDO begin to decompose at temperatures of 230°C, whereas all samples of diesel emulsion water average decomposes at a temperature of 110°C. In Thermal Gravimetric Analysis (TGA) testing sample numbers II is the best sample.